2019
DOI: 10.1016/j.jbiomech.2019.109400
|View full text |Cite
|
Sign up to set email alerts
|

The use of continuous spectral analysis for the assessment of postural stability changes after sports-related concussion

Abstract: The use of continuous spectral analysis for the assessment of postural stability changes after sports-related concussion. Journal of Biomechanics, 97.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…42 Another study showed significant differences only with the tandem stance component in concussed athletes at day 4 postinjury compared with preinjury. 70 Concussed adolescent athletes had significantly more sway/errors than controls an average of 11 days postinjury with complex tandem gait assessments and the ideal cut-point for total number of sway/errors for complex tandem gait was 5 (sensitivity 41%, specificity 90%). 42 The component of tandem gait with the greatest sensitivity was backward eyes closed (81%); the component with the greatest specificity was forward eyes open (99%).…”
Section: Paediatric-specificmentioning
confidence: 92%
“…42 Another study showed significant differences only with the tandem stance component in concussed athletes at day 4 postinjury compared with preinjury. 70 Concussed adolescent athletes had significantly more sway/errors than controls an average of 11 days postinjury with complex tandem gait assessments and the ideal cut-point for total number of sway/errors for complex tandem gait was 5 (sensitivity 41%, specificity 90%). 42 The component of tandem gait with the greatest sensitivity was backward eyes closed (81%); the component with the greatest specificity was forward eyes open (99%).…”
Section: Paediatric-specificmentioning
confidence: 92%
“…Postural stability is maintained through the integration of sensory information provided by the visual, proprioceptive, and vestibular systems ( Loughlin and Redfern., 2001 ). Those systems have different time delays in their control pathways, enabling their relative afferent contributions to be studied by identifying characteristic COP frequency responses ( Daniels et al, 2019 ). The frequency spectral energy can be obtained by performing a fast Fourier transform, which enables the researcher to convert wave graphs of COP movement as represented by amplitude (power) and time into a relationship between amplitude (power) and frequency (spectrum); the power included for each frequency is defined as the frequency spectral energy ( Tanaka et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this interpretation, the most important principal components (PCs) can be regarded as the dominant synergies of the complex motion, reducing the high dimensionality of the recorded data. Applied to joint angular time series, this provides a means to analyze the importance of individual joints to the whole of motion and to determine the magnitude and sign (i.e., phase) of the contribution of individual joints to the pattern (Cowley & Gates, 2017;Daniels et al, 2019;Noé et al, 2017).…”
mentioning
confidence: 99%